2008
DOI: 10.1021/om800683g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silica-Supported Compact Phosphines and Their Application to Rhodium-Catalyzed Hydrosilylation of Hindered Ketones with Triorganosilanes

Abstract: Solid-supported phosphine ligands silica−SMAPs {[silica gel 60N]−SMAP (1a) or [CARiACT Q-10]−SMAP (1b)}, which are composed of a caged, compact trialkylphosphine (SMAP) as a ligand and silica gel (silica gel 60N or CARiACT Q-10) as a support, were synthesized through surface functionalization. The supported phosphines (1a,b) were structurally characterized by solid-state 13C, 29Si, and 31P cross-polarization/magic angle spinning (CP/MAS) NMR spectroscopies and N2 adsorption measurements. Complexation of 1a,b w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…The reported data and further experiments provided evidence for a rhodium species only coordinated by one phosphine of [silica]-SMAP (10). 61,62 This trend was also seen in other publications where very bulky monodentate phosphines and isocyanides were used in homogeneous systems and proved to be very efficient ligands in rhodium-catalyzed hydrosilylation of ketones. 63−66 Very recently, research has focused on the application of rhodium-catalyzed hydrosilylation in ionic liquids.…”
Section: N-heterocyclicsupporting
confidence: 63%
“…The reported data and further experiments provided evidence for a rhodium species only coordinated by one phosphine of [silica]-SMAP (10). 61,62 This trend was also seen in other publications where very bulky monodentate phosphines and isocyanides were used in homogeneous systems and proved to be very efficient ligands in rhodium-catalyzed hydrosilylation of ketones. 63−66 Very recently, research has focused on the application of rhodium-catalyzed hydrosilylation in ionic liquids.…”
Section: N-heterocyclicsupporting
confidence: 63%
“…Nitrogen‐adsorption measurements of Silica‐3p‐TPP ([P]=0.20 mmol g −1 ) showed that the surface modification of the CARiACT Q10 silica gel with the tripod phosphane and the TMS groups resulted in a reasonable reduction of structural parameters, such as surface area (284 versus 271 m 2 g −1 ), pore diameter (17.8 versus 15.6 nm), and pore volume (1.32 versus 1.03 mL g −1 ) 17b. On the basis of the surface area value and the TPP loading, the surface P‐atom density for Silica‐3p‐TPP was calculated to be 0.44 nm −2 .…”
Section: Resultsmentioning
confidence: 99%
“…5 On the other hand, we have developed Silica‐SMAP, which is a silica‐supported “compact” phosphane ligand 6. 7 Because of its immobilized nature, this ligand forms 1:1 metal/P complexes exclusively with a range of transition‐metal species, despite its extreme compactness 7a,b. We demonstrated that the surface‐bound 1:1 metal/P complexes afford highly active catalysts for the hydrosilylation and the hydrogenation of ketones (with Rh),7ac and the directed ortho borylation of functionalized arenes (with Ir) 7df.…”
Section: Methodsmentioning
confidence: 91%